Upaya Guru Pendidikan Agama Islam Dalam Mengatasi Kenakalan Siswa SMK Ma’arif 4 Kebumen - Indah Inayaturrohmah; Nuraini Habibah (IAINU Kebumen, 2026)
This study aims to analyze and describe the efforts of Islamic Religious Education teachers in overcoming student delinquency at SMK Ma'arif 4 Kebumen, as well as to determine the level of success of these efforts. Using a descriptive qualitative approach, this study involved Islamic Religious Education teachers, Guidance and Counseling teachers, and students majoring in Industrial Mechanical Engineering as subjects. Data were collected through interviews, observations, and documentation, then analyzed using data reduction, data presentation, and drawing conclusions. The results of the study indicate that the efforts of Islamic Religious Education teachers include preventive measures (advice, teaching discipline through memorization), curative (advice, educational punishment, summons to the BK room, teacher approaches with students for minor delinquency; reprimands, discussions with parents and authorities, regular supervision for serious delinquency), and religious formation. The achievement of these efforts is significant, marked by students who are calmer, enjoy learning, and open to teachers, although behavioral changes require periodic time